Patterns and Impact of Hypoglycemia, Hyperglycemia, and Glucose Variability on Inpatients with Insulin-Treated Cystic Fibrosis-Related Diabetes. Issue 3 (September 2016) - Jones, Gregory; Chong, Zhou; Gilmour, Jennifer; Matheson, Christine; MacGregor, Gordon; Sainsbury, Christopher
Abstract Introduction Mortality in patients with cystic fibrosis-related diabetes (CFRD) is higher than that in patients with cystic fibrosis without diabetes. Hypoglycemia, hyperglycemia, and glucose variability confer excess mortality and morbidity in the general inpatient population with diabetes. Methods We investigated patterns of hypoglycemia and the association of hypoglycemia, hyperglycemia, and glucose variability with mortality and readmission rate in inpatients with CFRD. All capillary blood glucose (CBG) readings (measured using the Abbott Precision web system) of patients with insulin-treated CFRD measured within our health board between January 2009 and January 2015 were. Frequency and timing of hypoglycemia (<4 mmol/L) and was recorded. The effect of dysglycemia on readmission and mortality was investigated with survival analysis. Results Sixty-six patients were included. A total of 22, 711 CBG results were included in the initial analysis. Hypoglycemia was common with 1433 episodes (6.3%). Hypoglycemia ascertainment was highest between 2400 and 0600 h. Hypoglycemia was associated with a significantly higher rate of readmission or death over the 3.5-year follow-up period (P  = 0.03). There was no significant association between hyperglycemia or glucose variability and the rate of readmission and mortality. Conclusion Among inpatients with CFRD hypoglycemia is common and is associated with an increased composite endpoint of readmission and death. As with previously reported trends in general inpatient population this group shows a peak incidence of hypoglycemic during the night.